RISALAH MEDIASI SEBAGAI SYARAT FORMIL DALAM MENGAJUKAN GUGATAN PENGADILAN HUBUNGAN INDUSTRIAL - Raden Reza Faris Thrienandya; Andari Yurikosari (Fakultas Hukum Universitas Trisakti, 2022)
The PHI judge in decision Number 211/Pdt.Sus-PHI/2020/PN.Jkt.Pst) granted part of the Plaintiff's lawsuit, but the PHI Judge did not state that the PHI settlement process must be proven to have mediated by showing the minutes of mediation settlement as a formal requirement for filing a lawsuit at the Industrial Relations Court issued by an authorized official as a mediator to provide minutes of mediation settlement to the disputing parties. The type of research here is normative research with secondary data sources supported by primary data. The nature of descriptive research and conclusions with deductive reasoning. This research resulted in the conclusion that the judge's consideration of the mediation minutes in the decision was not in accordance with the applicable laws and regulations. Decision Number 211/Pdt.Sus-PHI/2020/PN.Jkt.Pst the judge did not heed the exceptions from the defendant so the judge continued to decide the case and rejected the defendant's exception regarding the processual exception.